2021
DOI: 10.1371/journal.pone.0260410
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Burnout Syndrome and other psychiatric disorders among health professionals during the COVID-19 pandemic: A systematic review and meta-analysis protocol

Abstract: Introduction Studies carried out during previous pandemics revealed an increase in the prevalence of Burnout Syndrome and other psychiatric disorders among health professionals. A high prevalence of psychiatric disorders is also observed in some health categories, during the COVID-19 pandemic. Objective This systematic review/meta-analysis study aims to assess the prevalence of Burnout Syndrome and other psychiatric disorders (depression, anxiety, stress, and insomnia) among health care professionals and oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 38 publications
0
3
1
Order By: Relevance
“…This is probably because the pandemic situation has worsened the burnout symptomatology among teachers due to the challenges they have had to face [ 49 , 50 , 51 ]. With respect to other studies conducted during the pandemic, the present results are higher than rates for healthcare professionals overall of 21% [ 52 ], and for nurses of 34.1% [ 53 ], groups that have been studied more extensively [ 54 ]. This is remarkable, as several studies have been concerned with the mental state of healthcare workers [ 55 , 56 , 57 , 58 ], but the mental state of teachers has not been investigated as much.…”
Section: Discussioncontrasting
confidence: 79%
“…This is probably because the pandemic situation has worsened the burnout symptomatology among teachers due to the challenges they have had to face [ 49 , 50 , 51 ]. With respect to other studies conducted during the pandemic, the present results are higher than rates for healthcare professionals overall of 21% [ 52 ], and for nurses of 34.1% [ 53 ], groups that have been studied more extensively [ 54 ]. This is remarkable, as several studies have been concerned with the mental state of healthcare workers [ 55 , 56 , 57 , 58 ], but the mental state of teachers has not been investigated as much.…”
Section: Discussioncontrasting
confidence: 79%
“…The progression of the infection and the maintenance of these stress levels for a long time has increased the chances of developing greater levels of anxiety, irritability and loneliness [33]. A condition of stress that, when predicting work burn-out events, undermines work performance and, consequently, care outcomes [34]. Despite the difficulties encountered by health care workers, not all of them are destined to suffer the effects of work-related stress, or experience job burnout or severe dissatisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…A similar study in Ireland found higher prevalence values for depression with a prevalence between 22 and 28% in the general population during the pandemic ( 31 ). It should also be noted that in countries such as Brazil, India, and the United States, variation was observed in the figures for depression in relation to the moment the data were collected during the pandemic, where an increase was presented during the peaks of COVID-19 contagion ( 32 ). A series of cases of psychotic depression in healthcare workers during the pandemic showed that a number of factors could influence the development of a mental disorder in at-risk populations, in this case, healthcare workers with significant pandemic-related stress ( 33 ).…”
Section: Discussionmentioning
confidence: 99%